2000
DOI: 10.1007/bf02723654
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-bacteriological study of neonatal septicemia in Hubli

Abstract: Septicemia is a leading cause of neonatal morbidity and mortality in India. In a study of 242 infants with septicemia conducted between March 1996 & June 1997 at Hubli, Karnataka, 43.39% infants had 'very early onset' sepsis (VOS), 40.08%, had 'early onset' sepsis (EOS), and 16.53% 'late onset' sepsis (LOS). 54.55% neonates had birth weight below 2000 g and 39.67% were born before 37 weeks of gestation. The cardiorespiratory signs and jaundice were the most frequent clinical features. The blood culture positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

53
108
7
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(176 citation statements)
references
References 14 publications
53
108
7
5
Order By: Relevance
“…Third generation cephalosporin resistance is now rampant and has been widely reported by recent studies. 3,4,7,8,10,15,16,17 Ceftizoxime revealed better sensitivity pattern against Pseudomonas aeruginosa (57%) in index study when compared to a recent study (25%). 18 Pseudomonas was sensitive to ciprofloxacin in only 47% isolates in our study as against reported sensitivity of 75% by Kumhar. 12 Recent studies reported increased resistance of Pseudomonas to ciprofloxacin varying from 10% to 40.8%.…”
Section: Discussionmentioning
confidence: 59%
“…Third generation cephalosporin resistance is now rampant and has been widely reported by recent studies. 3,4,7,8,10,15,16,17 Ceftizoxime revealed better sensitivity pattern against Pseudomonas aeruginosa (57%) in index study when compared to a recent study (25%). 18 Pseudomonas was sensitive to ciprofloxacin in only 47% isolates in our study as against reported sensitivity of 75% by Kumhar. 12 Recent studies reported increased resistance of Pseudomonas to ciprofloxacin varying from 10% to 40.8%.…”
Section: Discussionmentioning
confidence: 59%
“…Fungal, rickettsial, protozoal and viral infections also cause thrombocytopenia [6]. As this study was done only for bacterial isolate, there might be other cause as mentioned above may be associated with thrombocytopenia which did not show bacterial growth.…”
Section: Discussionmentioning
confidence: 89%
“…aureus, Staph. epidermidis, Group B Streptococci, Enterococcus faecalis, Entrobacter sp., Acinetobacter sp., Pseudomonas sp., Proteus sp., Citrobacter seen in developing countries [2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly seen clinical feature of neonatal sepsis was respiratory distress which was also associated in some cases with grunting in the study of Ghosh et al [14] , Tallur et al [20] also noted in their studies that cardiorespiratory signs are the commonest form of presentation. Other clinical features found in our study were jaundice, fever, vomiting and CNS symptoms which is affirmed by the study of Mohammad f. Ibraheem.…”
Section: Clinical Presentationmentioning
confidence: 99%